Stabilization of Organic–Inorganic Perovskite Layers by Partial Substitution of Iodide by Bromide in Methylammonium Lead Iodide. Issue 10 (3rd March 2016) - Ruess, Raffael; Benfer, Felix; Böcher, Felix; Stumpp, Martina; Schlettwein, Derck
Abstract: Thin films of the methylammonium lead halides CH3 NH3 Pb(I1− x Br x )3 are prepared on fluorine‐doped tin oxide substrates and exposed to humid air in the dark and under illumination. To characterize the stability of the materials, UV/Vis spectra are acquired at fixed intervals, accompanied by XRD, energy‐dispersive X‐ray spectroscopy, SEM, and confocal laser scanning microscopy. Different degradation mechanisms are observed depending on the environmental conditions. It is found that bromide can successfully suppress the transformation of the perovskite into the monohydrate, presumably owing to stronger hydrogen‐bonding interactions with the organic cation. However, under illumination in humid air, rather rapid decomposition of the perovskites was still observed, which is due to phase segregation. The use of increased bromide content in methylammonium lead halide absorbers is discussed in terms of their application in perovskite solar cells. Abstract : Waterproofing perovskites : The chemical stability of thin films of methylammonium lead iodide perovskite can be increased by the introduction of bromide ions. In particular, formation of the hydrate phase is suppressed (see figure). The role of hydrogen bonds in this stabilization is highlighted.